Optimization of Optoelectronic Charge Converter’s Parameters - Baluzis, A.; Sakalauskas, S. (Elektronika ir Elektrotechnika, 1999)
Theoretical simulation and experimental results of optical controlled Au-SiO2-Si(p)-SiO2-Au structure’s capacitance are presented in the paper. We had obtained, it is possible to optimize the effective SiO2 layer’s charge, the value of semiconductor doping, the value of photogeneration level, the length of optical signal wave and obtain maximum converter’s transmission coefficient, if we choose the thickness of SiO2 layer which determines maximum value of registered signal.